A construção da identidade profissional do professor de matemática no Projeto de Licenciaturas Parceladas da UNEMAT/MT - Sousa, Josimar de (2009)
The parceled Teaching Credential Project was a historical experience to the Médio Araguaia zone, in the sense that it mobilized an entire region in order for it to become reality and had the state system as partner because of the lack of a public policy until then, of education and professionalization of teachers with no credential. The purpose of this study was to identify which components of the Parceled Teaching Credential Project contributed for the constitution of the teaching professional identity and for giving a new meaning to the classroom practice of the Math teacher coming from the axis teaching by research. For such, the concepts of teachers education, teaching professional identity, teacher s research, research teacher and teaching knowledge were important. Five interviews were held with recently graduated Math teachers, inquiries were applied to three coordinators of the Math course and documents were used about the project. From the data reading to the light of the theory, the following categories were established for analysis: 1) Path personal life and professional experience. Subdivided in: a) professional choice; b) basic and college education; c) work conditions and socializing process; d) investment in the career and in the professional development; 2) Process of identity constitution from recently graduated teachers; 3) Teaching view and specific knowledge of Math; 4) The research as teacher s work. Subdivided in: a) monographs and b) the insertion of the research activity at school. The study indicated that the Project contributed to the reasoning by the teachers about the sense of being a Math teacher, the constitution of his/her professional identity, seeing through the teaching by research, the structuring axis of his/her work and how to give a new meaning of his/her practice in the classroom. From this study, it was possible to conclude that the Project is not the only component of the teaching being, because, the life path, the regional context are, also, components of the teaching professional identity and that the courses of initial education exert a meaningful role in the constitution of the professional life from the future teacher and in the process of constitution of his/her professional identity, strengthened by the lived experiences in his/her circulation environment, in this case, in the education space in the Parceled Teaching Credential Project and in the space of professional performance the schools